Emotional intelligence and academic achievement among first-year undergraduate university students: the mediating role of academic engagement - Bereded, Derib Gosim; Abebe, Amare Sahile; Negasi, Reda Darge (Frontiers in Education, 2025)
The purpose of this study was to investigate the relationship between emotional intelligence (EI) and academic achievement, with academic engagement serving as a mediator. A correlational research design was employed to achieve this objective. First-year regular undergraduate students attending Wollo University during the 2023/2024 academic year comprised the target population. The Trait Emotional Intelligence Questionnaires-Short Form (TEIQue-SF) and Utrecht Work Engagement Scale-Student Version (UWES-S) were used to collect data from 1,351 randomly selected students. The first-semester grade point average was used to assess academic achievement scores. The following analyses were performed: descriptive statistics, Pearson product–moment correlation, measurement model analysis to ascertain the reliability and validity of the measures used in the study, and structural equation modeling (SEM) analysis to test the relationships between the study variables. The results revealed that trait EI was positively related to academic engagement (r = 0.350), academic achievement (r = 0.407), and the relationship between academic engagement and academic achievement (r = 0.628). The measurement model analysis confirmed an acceptable level of reliability and construct validity for the TEIQue-SF and UWES-S measures. Findings showed that trait EI had a positive and direct effect on academic achievement and engagement. Trait EI and academic engagement accounted for 49.9% of the variance in academic achievement. Mediation analyses indicated that academic engagement partially mediates the effect of EI on students’ academic achievement (β = 0.220, p = 0.000). This suggests that the positive effect of EI on academic achievement is further enhanced by academic engagement. It is recommended that curriculum developers and educators focus on intervention strategies that foster students’ EI skills and academic engagement.